2021
DOI: 10.1016/j.ejogrb.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Circulating kisspeptin and anti-müllerian hormone levels, and insulin resistance in women with polycystic ovary syndrome: A systematic review, meta-analysis, and meta-regression

Abstract: Objective: This systematic review and meta-analysis aimed to summarize the available evidence regarding circulating kisspeptin and anti-müllerian hormone (AMH) and the homeostasis model assessment of insulin resistance (HOMA-IR) index in adolescents and women with and without polycystic ovary syndrome (PCOS).Method: We performed a comprehensive literature search in Medline, Embase, Cochrane, Scopus, and Web of Science for studies evaluating circulating kisspeptin levels in women with and without PCOS published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Liu et al [ 37 ] have proposed a broader hypothesis in that kisspeptin can be regarded as an independent biomarker of PCOS. This proposition was made on the basis of a large meta-analysis (1282 participants: 699 patients and 583 controls) which noted that serum kisspeptin levels were higher in patients with PCOS compared to non-PCOS patients.…”
Section: Kisspeptin and Pcosmentioning
confidence: 99%
“…Liu et al [ 37 ] have proposed a broader hypothesis in that kisspeptin can be regarded as an independent biomarker of PCOS. This proposition was made on the basis of a large meta-analysis (1282 participants: 699 patients and 583 controls) which noted that serum kisspeptin levels were higher in patients with PCOS compared to non-PCOS patients.…”
Section: Kisspeptin and Pcosmentioning
confidence: 99%
“…Out of 12 studies in patients with PCOS, eight showed significantly higher serum levels of kisspeptin. Pérez-López et al 23 broadening hypothesis states that kisspeptin can be viewed as a separate PCOS biomarker. This claim was based on a comprehensive meta-analysis that included 1282 people, including 699 patients and 583 controls, and found that blood kisspeptin levels were greater in PCOS patients than in non-PCOS patients.…”
Section: Kisspeptin a N D Pcosmentioning
confidence: 99%
“…128,[131][132][133] In addition, KNDy neurons are considered to at least partly mediate sex steroid negative feedback on GnRH secretion. 129,132,134 Women with PCOS appear to have elevated circulating kisspeptin levels (standardized mean difference 1.15 with 95% confidence interval 0.68-1.62) 135 ; the source of this kisspeptin is unknown but is unlikely to be the brain. Women with PCOS may be more likely to harbor the GG genotype of the kisspeptin gene polymorphism rs4889.…”
Section: Potential Role Of Kisspeptin Neurons In Pcosrelated Gnrh Neu...mentioning
confidence: 99%